Ultra‐endurance exercise induces stress and inflammation and affects circulating hematopoietic progenitor cell function. Issue 5 (1st December 2014) - Stelzer, I.; Kröpfl, J. M.; Fuchs, R.; Pekovits, K.; Mangge, H.; Raggam, R. B.; Gruber, H.‐J.; Prüller, F.; Hofmann, P.; Truschnig‐Wilders, M.; Obermayer‐Pietsch, B.; Haushofer, A. C.; et al.
Abstract : Although amateur sports have become increasingly competitive within recent decades, there are as yet few studies on the possible health risks for athletes. This study aims to determine the impact of ultra‐endurance exercise‐induced stress on the number and function of circulating hematopoietic progenitor cells (CPCs) and hematological, inflammatory, clinical, metabolic, and stress parameters in moderately trained amateur athletes. Following ultra‐endurance exercise, there were significant increases in leukocytes, platelets, interleukin‐6, fibrinogen, tissue enzymes, blood lactate, serum cortisol, and matrix metalloproteinase‐9. Ultra‐endurance exercise did not influence the number of CPCs but resulted in a highly significant decline of CPC functionality after the competition. Furthermore, Epstein‐Barr virus was seen to be reactivated in one of seven athletes. The link between exercise‐induced stress and decline of CPC functionality is supported by a negative correlation between cortisol and CPC function. We conclude that ultra‐endurance exercise induces metabolic stress and an inflammatory response that affects not only mature hematopoietic cells but also the function of the immature hematopoietic stem and progenitor cell fraction, which make up the immune system and provide for regeneration.